Resonant X‐ray scattering studies of epitaxial complex oxide thin films. (18th January 2013) - Perret, Edith; Park, Changyong; Fong, Dillon D.; Chang, Kee‐Chul; Ingram, Brian J.; Eastman, Jeffrey A.; Baldo, Peter M.; Fuoss, Paul H.
<x xml:space="preserve">Abstract</x> Resonant anomalous X‐ray reflectivity (RAXR) is a powerful technique for measuring element‐specific distribution profiles across surfaces and buried interfaces. Here, the RAXR technique is applied to characterize a complex oxide heterostructure, La0.6Sr0.4Co0.2Fe0.8O3−δ, on NdGaO3, and the effects of data sampling and model‐dependent fitting procedures on the extracted elemental distribution profile are evaluated. The strontium profile through a 3.5 nm‐thick film at 973 K and at an oxygen partial pressure of 150 Torr (1 Torr = 133.32 Pa) was determined from the measured RAXR spectra. The results demonstrate that in situ RAXR measurements can provide key insights into temperature‐ and environment‐dependent elemental segregation processes, relevant, for example, in assessing the cathode performance of solid oxide fuel cells.